Spatial-channel transformer network based on mask-RCNN for efficient mushroom instance segmentation - Wang, Jiaoling; Song, Weidong; Zheng, Wengang; Feng, Qingchun; Wang, Mingfei; Zhao, Chunjiang (International Journal of Agricultural and Biological Engineering, 2024)
Edible mushrooms are rich in nutrients; however, harvesting mainly relies on manual labor. Coarse localization of each mushroom is necessary to enable a robotic arm to accurately pick edible mushrooms. Previous studies used detection algorithms that did not consider mushroom pixel-level information. When these algorithms are combined with a depth map, the information is lost. Moreover, in instance segmentation algorithms, convolutional neural network (CNN)-based methods are lightweight, and the extracted features are not correlated. To guarantee real-time location detection and improve the accuracy of mushroom segmentation, this study proposed a new spatial-channel transformer network model based on Mask-CNN (SCT-Mask-RCNN). The fusion of Mask-RCNN with the self-attention mechanism extracts the global correlation outcomes of image features from the channel and spatial dimensions. Subsequently, Mask-RCNN was used to maintain a lightweight structure and extract local features using a spatial pooling pyramidal structure to achieve multiscale local feature fusion and improve detection accuracy. The results showed that the SCT-Mask-RCNN method achieved a segmentation accuracy of 0.750 on segm_Precision_mAP and detection accuracy of 0.638 on Bbox_Precision_mAP. Compared to existing methods, the proposed method improved the accuracy of the evaluation metrics Bbox_Precision_mAP and segm_Precision_mAP by over 2% and 5%, respectively. Key words: edible mushrooms; picking; instance segmentation; deep learning; algorithm DOI: 10.25165/j.ijabe.20241704.8987 Citation: Wang J L, Song W D, Zheng W G, Feng Q C, Wang M F, Zhao C J. Spatial-channel transformer network based on mask-RCNN for efficient mushroom instance segmentation. Int J Agric & Biol Eng, 2024; 17(4): 227–235.